2019
DOI: 10.1155/2019/3505034
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rhodomyrtus tomentosa (Aiton) Hassk. Fruits in Downregulation of Mast Cells-Mediated Allergic Responses

Abstract: Rhodomyrtus tomentosa, a flowering plant of Myrtaceae family from southern and southeastern Asia, was known to possess a rich source of structurally diverse and various biological activities. In this study, the inhibitory effect of R. tomentosa fruit extract (RFE) on allergic responses in calcium ionophore A23187-activated RBL-2H3 mast cells was investigated. The result showed that RFE was able to inhibit mast cell degranulation via decreasing β-hexosaminidase release and intracellular Ca2+ elevation at the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Nr, normal; OVA-CT, control treated with only ovalbumin; Dexa., dexamethasone; SB, Scutellaria baicalensis Georgi extract. * p < 0.05, * * p < 0.01, and * * * p < 0.001 showed a significant difference from OVA-CT. degranulation via decreasing β-hexosaminidase release [23]. In our study, baicalein showed similar results inhibiting the release of β-hexosaminidase from IgE-stimulated RBL-2H3 mast cell showing significant inhibitory activity at 12.5 μg•mL −1 and 25 μg•mL −1 .…”
Section: Discussionsupporting
confidence: 80%
“…Nr, normal; OVA-CT, control treated with only ovalbumin; Dexa., dexamethasone; SB, Scutellaria baicalensis Georgi extract. * p < 0.05, * * p < 0.01, and * * * p < 0.001 showed a significant difference from OVA-CT. degranulation via decreasing β-hexosaminidase release [23]. In our study, baicalein showed similar results inhibiting the release of β-hexosaminidase from IgE-stimulated RBL-2H3 mast cell showing significant inhibitory activity at 12.5 μg•mL −1 and 25 μg•mL −1 .…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, various pharmaceutical values of R. tomentosa including anti‐inflammatory, antioxidant, antimicrobial, anticancer, anti‐diabetic, anti‐ulcerogenic, antidepressant, and anti‐atherosclerotic activities have been evidenced in different experimental models (Vo & Ngo, ). In our previous report, R. tomentosa fruit extract (RFE) has been shown to suppress allergic responses in the activated mast cells (Vo, Kim, Ngo, & Ngo, ). This activity of RFE was suggested to be due to its biologically active components, especially phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…2 In addition to these nutrients, rose myrtle fruit contains a number of bioactive ingredients, including triterpenoids, flavonoids, phenols, and meroterpenoids. 3 Furthermore, studies have shown that rose myrtle fruit has many beneficial functions, such as antiallergic, 4 antiinflammatory, 5 anti-oxidant, 6,7 and anti-tumor effects. 7 Because of the known health benefits reported in ancient and modern literature, rose myrtle fruit has been used to make dietary supplements, herbal medicines, beverages, wines, jams, syrups, and cosmetics in recent decades 3,8 For example, a recent study showed that consumption of rose myrtle fruit juice suppressed hypercholesterolemia and atherosclerosis in rats fed with a high-fat high-cholesterol diet.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition to these nutrients, rose myrtle fruit contains a number of bioactive ingredients, including triterpenoids, flavonoids, phenols, and meroterpenoids . Furthermore, studies have shown that rose myrtle fruit has many beneficial functions, such as antiallergic, anti-inflammatory, anti-oxidant, , and anti-tumor effects …”
Section: Introductionmentioning
confidence: 99%